Understanding and breaking the intergenerational cycle of abuse in families enrolled in routine mental health services: study protocol for a randomized controlled trial and two non-interventional trials investigating mechanisms of change within the UBICA II consortium - Neukel, Corinne; Bermpohl, F.; Kaess, Michael; Taubner, Svenja; Boedeker, K.; Williams, Katharina; Dempfle, A.; Herpertz, Sabine (Trials, 2021)
Parents’ mental illness (MI) and parental history of early life maltreatment (ELM) are known to be significant risk factors for poor parenting while poor parenting is a crucial mediator of the intergenerational continuity of child maltreatment. Hence, maltreatment prevention programs for families with an MI parent, which pay particular attention to experiences of ELM in the parent, are urgently needed. Parental mentalizing was previously found to mediate successful parenting. Interventions aimed at improving the parental mentalizing capacity reduced maltreatment risk in parents. The aim of the present study is to investigate the effectiveness of a mentalization-based parenting-counseling in acutely mentally ill parents currently treated at a psychiatric hospital.
Gesehen am 15.12.2021